PEMANFAATAN RUMPUT SEBAGAI KOMPOS UNTUK KESUBURAN TANAH BEKAS GALIAN BATU DENGAN UJI TANAMAN KAKAO (Theobroma cacao L.) - Rossy Mirasari; Sri Ngapiyatun (Politeknik Pertanian Negeri Samarinda, 2017)
Research of exploiting of grass as compost for the fertility of soil of ex- stone dig with crop test of cocoa (Theobroma Cacao L.) discussed in this article. Target of this research is to know element content of hara at made compost, do the compost with quality and can repair fertility of soil of ex- stone dig with crop test of kakao. Compost made of chopped grass materials then enhanced with activator of EM4. Materials compost included into coarse bag then bound and its underside is given hole to conduct water. During process of compost, coarse bag put down above dry pallet and given wings of to avoid sunshine and rainwater. Process of compost during 14 day. Compost told to mature or become if black compost colour, aroma like ground aroma, crumb tekstur, normal temperature (equal to room temperature), and value of C/N ratio about 20 - 30. Result of research indicate that yielded compost with quality goodness, seen from result of chemical analysis show content of C/N compost 7,6, pH ( H2O) 6,86, pH ( KCl) 6,78 and element content of hara complete micro and macro. While soil of ex- stone dig given by treatment of compost also show result of good chemical analysis. Proven so that compost can repair fertility of soil of ex- stone dig. Crop parameter show different result of reality at all of high good parameter of crop, amount of leaf, bar diameter ( age 2, 4, 6, 8 week after moving to plant) and wide of leaf by the end of perception show treatment of stone dig soil with addition of compost (Kp) better than pure stone dig soil without treatment (K0).